The Challenges of Using Integrated Technology in the Classroom (LEARNing Landscapes, 2018)
In this interview, ICT consultant Kish Gué shares his thoughts on how teachers can integrate technology in the classroom. In view of ever-changing technological advances, he believes that teachers should switch to learning at the same time as their students as opposed to teaching them about technology. He provides examples of projects that have successfully integrated technology and gives advice to novice teachers on how to best use technology in their teaching. He explains that parents have an important role in ensuring that their kids become good “digital citizens” who use the Internet safely and responsibly. Finally, he shares what his own daughter has taught him about technology.
Keywords: technology integration; classroom technology; digital citizenship; teacher vulnerability and technology